Rynek motoryzacyjny w Polsce w latach 2015-2020 - Aleksandra Drozd (Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2022)
The aim of the article is to assess the condition of the automotive sector in Po-land. The main research problem was to identify barriers to the development of the au-tomotive market. The period between 2015 and2020 was analyzed. Data is collected eve-ry year. In the course of the research it was established that the automotive market is a constantly developing area. The barriers to development include the crisis in the semi-conductor market, the departure from internal combustion engines and random situa-tions such as war or pandemic. In the period 2015-2020, the Skoda brand is the leader in passenger car sales. In turn, Fiat boasts the highest sales of trucks.(original abstract)